Genetic association of the human GAP43 gene with schizophrenia in a Northeast Chinese Han population - Luan, Zhilin (Indian J Psychiatry, 2020)
BACKGROUND: GAP43, a membrane phosphoprotein with high expression level in the developing brains, plays an important role in higher integrative functions of the brain. MATERIALS AND METHODS: To explore the association of GAP43 with schizophrenia, 11 single-nucleotide polymorphisms (SNPs) were examined in a Northeast Chinese Han sample set consisting of 741 schizophrenia patients and 1330 healthy controls. RESULTS: The results showed that three SNPs were associated with schizophrenia (rs2028248, rs6790048, and rs2164930). Haplotype analysis also revealed a significant association of a strong linkage disequilibrium block (rs2164930-rs11926976-rs16823991) with schizophrenia. CONCLUSION: The current findings suggested that the human GAP43 gene may be a susceptibility gene for schizophrenia.